THE SOCIAL-PSYCHOLOGICAL DETERMINANTS OF PREGNANT WOMEN’ SELF-ESTEEM - Martyniuk, Iryna (PSYCHOLOGICAL JOURNAL, 2020)
The psychology of motherhood is one of the most complex and little-studied branches of modern science. Such studies are important because of existing grave demographic problems associated with falling birth rates, the large number of divorces, the increasing number of children abandoned by their parents or cases of child abuse, insufficient social and psychological assistance for families, and especially for women in labour.The holistic psychological approach is relevant to studies of motherhood and social-psychological determinants forming pregnant women’s self-esteem, because psychological problems of motherhood and early childhood are in demand on the background of modern advances in medicine, physiology, gynaecology and obstetrics, improved scientific-technical help at childbirth and neonatal practices.The article studies pregnant women’s self-esteem, in particular, by taking into account such characteristics as women’s reproductive health, psychological-emotional states during pregnancy, psychological readiness for motherhood, social environment, social support, self-realization in the professional sphere, social guarantees given by employers.The article proposes the theoretical model covering social-psychological determinants of pregnant women’s self-esteem, which takes into account both the general social-psychological factors of life and the sphere of life specific for a modern pregnant woman. The presented determinants affect a woman’s self-esteem before / during pregnancy, after childbirth and form her attitude to herself and to her role as a mother in family and society. The purpose of this theoretical model is to analyze the impact of socio-psychological determinants on pregnant women’s self-esteem.Pregnant women’s self-esteem is a multilevel structure, which parts are studied in many sciences (psychology, sociology, demography, medicine - (gynaecology, obstetrics, neonatology, prenatal psychology), and covers all areas of pregnant women’ life.